HTML and CSS video quickstart - Hadlock, Kris (Peachpit Press, 2013)
"The video companion to the bestselling HTML and CSS: Visual QuickStart Guide, Eighth Edition, is based on material by Elizabeth Castro and Bruce Hyslop and presented by Kris Hadlock. These short, tasked-based videos provide the necessary groundwork to understanding the fundamentals of HTML described in the book. The videos look at HTML's commonly used structural elements for developing a website and step you through creating a basic Web page with the absolute essentials. You'll look at elements, attributes, and CSS style sheets; learn how to add a web form to your page to style form elements; add a web form to your page to style form elements; debug and test code; and more. This video will have you up and running with HTML in no time."--Resource description page.
Title from resource description page (viewed Oct. 28, 2013)
Keywords: HTML (Document markup language); Cascading style sheets; Web sites -- Design; HTML (Langage de balisage); Feuilles de style en cascade; Sites Web; Conception; HTML; Web sites; Design; Electronic videos